1984
DOI: 10.1002/lipi.19840860310
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Discriminant Analysis of Fatty Acids from Male Scalp Hair Lipids

Abstract: Lipids extracted from the scalp hair of Caucasian boys, teenagers and adults and Black Teenagers of a boarding school, were saponified and the groups compared with respect to the total fatty acids by multiple discriminant analysis. The lipid yields from Black ranged higher than those from Caucasians. Among the Caucasians, differences based on age were not significant. The total acids of hair lipids from Blacks differed significantly as compared to those of the White groups, a trend also supported by analyses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The CaCO 3 and KNO 3 crystallization experiments revealed that the different surface modification strategies had marked effects on the nucleating properties of human and dog hairs. The outer surface of the hair is the cuticle layer, which consists of ≈75% highly cross-linked keratin and ≈25% lipids, of which 18-methyleicosanoic acid is the most abundant . Lipids are either free (unbound) or covalently attached to keratin through thioester linkages (bound).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CaCO 3 and KNO 3 crystallization experiments revealed that the different surface modification strategies had marked effects on the nucleating properties of human and dog hairs. The outer surface of the hair is the cuticle layer, which consists of ≈75% highly cross-linked keratin and ≈25% lipids, of which 18-methyleicosanoic acid is the most abundant . Lipids are either free (unbound) or covalently attached to keratin through thioester linkages (bound).…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of surface chemistry to the behavior of the hairs was investigated by employing three surface treatment strategies by immersion in: (i) ethanol, (ii) petroleum ether, and (iii) hydrogen peroxide before water rinsing (Section S1.1). Petroleum ether removes lipids from the surface, ethanol removes lipids and denatures proteins, and hydrogen peroxide oxidizes the proteins on the hair surface, altering its chemistry and surface charge. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important contribution of this fatty acid has been also reported in the lipids from scalp hair bulbs. [41][42] Tunneling spectroscopy is now recognized to be a very sensitive tool to detect adsorbed species on the oxide surface. The sensitivity is high enough to detect less than 1013 molecules/cm2, which corresponds to a fraction of a monolayer of the surface.44 •45 The selective detection of the fatty acids in the benzene phase of the sweat is because of this high sensitivity for carboxylic acids.…”
Section: Resultsmentioning
confidence: 99%